Oral squamous cell carcinoma of the tongue: Prospective and objective speech evaluation of patients undergoing surgical therapy. Issue 7 (6th August 2015) - Riemann, Max; Knipfer, Christian; Rohde, Maximilian; Adler, Werner; Schuster, Maria; Noeth, Elmar; Oetter, Nico; Shams, Nima; Neukam, Friedrich‐Wilhelm; Stelzle, Florian
Abstract: Background: Prospective speech intelligibility assessments lack objectivity in patients undergoing surgery for oral squamous cell carcinoma (OSCC) of the tongue. Methods: Speech intelligibility was measured based on word recognition by means of an automatic and objective speech recognition system preoperatively, and 14 to 20 days, and 3 months, 6 months, and 12 months postoperatively. The study comprised 25 patients with OSCC of the tongue and a healthy control group ( n = 40). Results: Patients yielded significant speech impairments compared to the healthy control group both before surgery and after 12 months ( p ≤ .002). The speech intelligibility of the patients decreased significantly 14 to 20 days after surgery ( p < .001) but realigned to preoperative values after 12 months ( p = .159). Preservation of the tip of the tongue resulted in significantly higher word recognition after 12 months ( p = .007; Δword recognition = 16.29). Conclusion: Having OSSC of the tongue results in a significant impairment of speech intelligibility. The preservation of the tip of the tongue seems to be a central factor concerning the recovery of speech. © 2015 Wiley Periodicals, Inc. Head Neck 38: 993–1001, 2016